Exosomes-Coated miR-34a Displays Potent Antitumor Activity in Pancreatic Cancer Both in vitro and in vivo - Zuo L; Tao H; Xu H; Li C; Qiao G; Guo M; Cao S; Liu M; Lin X (Dove Medical Press, 2020)
Ling Zuo,1 Hongyu Tao,2 Huanli Xu,2 Cong Li,2 Gan Qiao,1,3 Mingyue Guo,1 Shousong Cao,1 Minghua Liu,1 Xiukun Lin1 1Department of Pharmacology, School of Pharmacy, Southwest Medical University, Luzhou, Sichuan 646000, People’s Republic of China; 2Department of Pharmacology, School of Basic Medicine, Capital Medical University, Beijing 100069, People’s Republic of China; 3Central Nervous System Drug Key Laboratory of Sichuan Province, Luzhou, Sichuan 646000, People’s Republic of ChinaCorrespondence: Xiukun Lin; Minghua Liu Tel +86 830 316 2291; +86 830 319 3872Email xiukunLin@126.com; liumhvip@163.comPurpose: MiR-34a, which acts as an important tumor suppressor gene, plays an important role in pancreatic cancer. However, the therapeutic application of miR-34a is limited by the lack of an effective delivery system. In the present study, we synthesize exosomes-coated miR-34a (exomiR-34a), and the anticancer effect of exomiR-34a was evaluated in pancreatic cancer.Materials and Methods: An ultrasound approach was used to synthesize exomiR-34a, and its transfection efficiency was examined by confocal microscopy and flow cytometry. The level of miR-34a and its targeted gene Bcl-2 was detected by real-time quantitative PCR (qRT-PCR). MTT analysis was performed to determine the effect of exomiR-34a on the growth of pancreatic cancer cells. Annexin-V/PI double staining and Western blot analysis were carried out to determine the apoptosis of the pancreatic cancer cells. The xenograft nude mice model bearing human pancreatic cancer Panc28 cells was used to determine the antitumor effect of exomiR-34a in vivo.Results: The exomiR-34a could cross the cell membrane efficiently, and downregulated the expression of the targeted gene Bcl-2. Treatment with exomiR-34a inhibited the growth of the pancreatic cancer cells significantly and the nanoparticles also induced apoptosis in cancer cells via affecting the expression of apoptotic-related genes. In vivo study using xenograft nude mice bearing Panc28 cancer cells revealed that exomiR-34a suppressed the growth of tumors significantly.Conclusion: ExomiR-34a can inhibit the growth of pancreatic cancer both in vitro and in vivo. Targeting miR-34a is a promising strategy for the treatment of pancreatic cancer. ExomiR-34a has the potential to be developed as a novel anticancer agent for the treatment of human pancreatic malignancy.Keywords: pancreatic cancer, miR-34a, exosomes, Bcl-2, anticancer